2020
DOI: 10.1007/s40430-020-02289-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meridian plane dip angle of the variable pitch inducer blade on cavitation performance of high-speed centrifugal pump

Abstract: To study the effect of the dip angle of the inducer blade section in the meridian plane on the cavitation performance of the high-speed centrifugal pump, four schemes of the inducer have been considered only by changing the dip angle of the blade section in the meridian plane while keeping the other geometrical parameters unchanged. Based on the RNG k-ɛ turbulence model and Zwart-Gerber-Belamri cavitation model, three-dimensional numerical simulation of a high-speed centrifugal pump is carried out. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The Schnerr-Sauer model, Zwart model, and Kunz model are the most commonly used cavitation models. [22][23][24][25] In this study, we use the Zwart model since it can work better at high flow rates and it has a more stable computation speed and better convergence. 26 Although the Schnerr-Sauer model can also work for high-speed flow, 27 the variable setting for the evaporation coefficient and condensation coefficient for different cavitation coefficient conditions in the Schnerr-Sauer model can be ignored in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The Schnerr-Sauer model, Zwart model, and Kunz model are the most commonly used cavitation models. [22][23][24][25] In this study, we use the Zwart model since it can work better at high flow rates and it has a more stable computation speed and better convergence. 26 Although the Schnerr-Sauer model can also work for high-speed flow, 27 the variable setting for the evaporation coefficient and condensation coefficient for different cavitation coefficient conditions in the Schnerr-Sauer model can be ignored in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The geometric parameters of the impeller passages are parameterized by drawing the blade installation angle (β) and the relative streamline length (la) on a graph using parametrized blade profiles, which have a relationship expressed by a differential equation in equation (2). For this optimization design, a total of 15 geometric parameters of the passages are selected, including the inlet radius of the blade on the front cover (RS), inlet radius of the blade on the back cover (Rh), inlet edge radius (Rle), and the utilization of fourth-order Bezier curves to control the blade profiles of the shroud, middle, and hub with 12 Y-axis input parameters of control points.…”
Section: Parametrization Of Impeller Blade Geometrymentioning
confidence: 99%
“…Scholars have found that cavitation is the root cause of these phenomena. Cavitation induces non-steady blade loads and inter-blade interactions in high-speed centrifugal pumps, leading to asymmetric voids in blade passages [2]. Therefore, improving the cavitation resistance of high-speed centrifugal pumps under extreme conditions remains a pressing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The head generated by the inducer can reduce the pump's Net Positive Suction Head (NPSH) and this will improve the pump's anti-cavitation performance [3][4][5][6][7][8][9][10]. The design of the inducer will affect the anti-cavitation performance of the pump [11][12][13]. The TC value of the inducer will affect the flow performance inside the inducer.…”
Section: Introductionmentioning
confidence: 99%